Regulating Indigenous Culture as a Tourism Economic Resource - Made Suksma Prijandhini Devi Salain; David Isles; I Gusti Ngurah Wairocana (Faculty of law Udayana University, 2017)
There have been some cases indicating the dissatisfaction of traditional communities with regards to tourism that does not economically contribute to their cultural activities. The legal issue raised in this writing is the lack of, or maybe the abstention of, a regulation that specifically regulates indigenous culture as a tourism economic resource. This article is aimed at describing and analyzing relevant international and national instruments that regulate the issues of indigenous culture and economic activities of tourism. The cases of Indonesia, especially Bali, compared with Australia are the focus of this article. It has been found that Indonesian laws and regulations are insufficient to protect culture as a tourism economic resource. In contrast, Australia has adopted a trichotomous approach wherein economic, social and cultural factors are separate and can be managed separately, an approach that has had mixed results.